Fabrication of Bone Scaffolds from Cockle Shell Waste - Siti Hajar, Saharudin; Jun Haslinda, Shariffuddin; Noor Ida Amalina, Ahamad Nordin (John Wiley & Sons, 2019)
Bone scaffold is a three‐dimensional structure composed of materials that could enhance bone regeneration. Bone scaffolds were prepared using freeze‐drying by varying the cockle shell powder concentration where sodium alginate acted as matrix. The scaffolds were then characterized by X‐ray diffraction, Fourier transform infrared spectroscopy, scanning electron microscopy, energy‐dispersive X‐ray spectroscopy, texture analyzer, and liquid displacement method. The bioactivity of the scaffolds was evaluated by immersion into a simulated body fluid solution. Cockle shell powder concentrations affected the bone scaffold characteristics. The increment of the powder concentrations improved the physicochemical properties and bioactivity of the scaffolds.